Ritual and social dynamics in Christian and Islamic preaching - Conrad, Ruth; Hardenberg, Roland; Miethner, Hanna; Stille, Max (Bloomsbury Academic, 2025)
"Explores the socio-cultural dynamics of religious speeches through an analysis of Christian and Islamic sermons and preachers"--